Knowledge Sharing Practices: A Case Study at Malaysia's Healthcare Research Institutes / Ramlee Abdul Rahman - Abdul Rahman, Ramlee (2011)
Knowledge sharing is essential in the implementation of any knowledge management initiative. The real sharing required is between the employees and their co-workers. The actual success depends on individuals' willingness to encourage and share their organisational knowledge through internal organisational social exchanges. The process requires the element of reciprocal arrangement and trust. It requires intra-team trust and intra-team relational bonds, leadership and also intercultural training that foster regular and frequent mutual cross-cultural exchange of ideas. The real advantage of knowledge management initiatives can be realised by truly empowering the employees. The main objective of the study was to basically investigate the perception of the researchers and officers within the National Institutes of Health Malaysia (NIH) with regards to their understanding of knowledge sharing practices in their respective environment. Hence, among the questions under studied were such as, what are the perceptions of the respondents with regard to the knowledge sharing practices in their respective institutions? What are the benefits for knowledge sharing practices as perceived by them? What are their perceived organisational knowledge sharing practices motivating factors? Also, what are the hindering factors? This study employed survey research method to obtain the perception of the researchers and officers of the NIH with regards to knowledge sharing practices. The questionnaire was distributed to 400 respondents from the six research institutes under NIH, namely Institute for Medical Research (IMR), Institute for Public Health (IPH), Network for Clinical Research Centres (CRC), Institute for Health Management (IHM), Institute for Health Systems Research (IHSR) and Institute for Health Promotion (IHP). The responses seem to indicate in essence, the arguments with regards to knowledge sharing always hinge within the context of encouraging and rewarding the practices of organisational knowledge sharing. The findings seem to also suggest four factors, Environment and Infrastructure, Management Support, Culture and Technology as significant determinants in influencing the organisational knowledge sharing practices among the employees. However, the study only deliberates on the perceptual aspect of the issue, and specifically from the individuals' opinion and sentiment.